2017
DOI: 10.1128/aac.01013-16
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Based bla OXA-48 -Like Variants in Shewanella Species Isolates from Food-Producing Animals, Fish, and the Aquatic Environment

Abstract: Carbapenems are considered last-resort antibiotics in health care. Increasing reports of carbapenemase-producing bacteria in food-producing animals and in the environment indicate the importance of this phenomenon in public health. Surveillance for carbapenemase genes and carbapenemase-producing bacteria in Dutch food-producing animals, environmental freshwater, and imported ornamental fish revealed several chromosome-based bla OXA-48 -like variants in Shewanella spp., including two new alleles, bla OXA-514 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…These bacteria are generally susceptible to third and fourth generation cephalosporins, carbapenems, beta-lactamase inhibitor combinations, aminoglycosides, chloramphenicol, erythromycin, aztreonam and quinolones [2,5,6]. However, resistance to these drugs is increasing due to the presence in their chromosome of class D beta-lactamase encoding genes (bla OXA ) conferring resistance to carbapenems, class C beta-lactamases (bla AmpC ) which decrease the susceptibility to cephalosporins and qnr genes responsible for resistance to quinolones [4,[7][8][9][10][11][12][13][14]. Furthermore, resistance to colistin, currently a last-resort antibiotic in human medicine, has been reported as well, due to the presence of the chromosomal eptA gene encoding for phosphoethanolamine transferase [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These bacteria are generally susceptible to third and fourth generation cephalosporins, carbapenems, beta-lactamase inhibitor combinations, aminoglycosides, chloramphenicol, erythromycin, aztreonam and quinolones [2,5,6]. However, resistance to these drugs is increasing due to the presence in their chromosome of class D beta-lactamase encoding genes (bla OXA ) conferring resistance to carbapenems, class C beta-lactamases (bla AmpC ) which decrease the susceptibility to cephalosporins and qnr genes responsible for resistance to quinolones [4,[7][8][9][10][11][12][13][14]. Furthermore, resistance to colistin, currently a last-resort antibiotic in human medicine, has been reported as well, due to the presence of the chromosomal eptA gene encoding for phosphoethanolamine transferase [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It harbors a genome containing several MGEs such as plasmids, superintegrons and insertion sequences (ISs) carrying cargo genes, particularly resistance and virulence genes [21]. Tetracyclines, aminoglycosides, third generation cephalosporins and fluoroquinolones are generally used as antibiotic therapy in human vibriosis outbreaks [13,22] but, several cases of multidrug-resistant (MDR) vibrios are reported in literature even to the last-resort antibiotics used in human medicine such as carbapenems [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Seafood imported from Southeast Asia was previously reported to contain carbapenemase-producing organisms; among aquatic microorganisms, however, such resistance genes are often encoded chromosomally in nonpathogenic organisms and therefore represent little cause for concern with respect to public health (8,9). More recently, bla VIM-1 was reported on a plasmid in Escherichia coli and bla IMI-1 was found to be chromosomally located in an E. cloacae complex isolated from seafood sources (10,11).…”
mentioning
confidence: 99%
“…The isolate was susceptible to ampicillin/sulbactam, piperacillin/tazobactam, imipenem, third‐generation cephalosporin and fourth‐generation cephalosporin. Various oxacillinase genes ( bla OXA ) have been detected in Shewanella species regardless of phenotypic resistance pattern (Ceccarelli et al, ). In our study, bla OXA‐416 was identified from the genome of S. xiamenensis ZYW1.…”
Section: Resultsmentioning
confidence: 99%